Model of Corporate Value Improvement Through Investment Opportunity in Manufacturing Company Sector - Faozi, Imam; Ghoniyah, Nunung (International Research Journal of Business Studies, 2019)
This study aims to analyze the significance of the direct and indirect effect of institutional ownership (INST), profitability (ROI), funding policy (DER), and dividend policy (Tobin’s Q) through investment opportunity (MV/BVE). The research data used 21 samples of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2012-2016 period. Data analysis used path analysis with the help of EViews 9 and Sobel test to know the effect of investment opportunity as an intervening variable. The interpretation findings of the first line analysis model show that Profitability directly affects positively and significantly on Corporate Value. Whereas, based on second-line analysis model, Funding Policy and Dividend Policy indirectly have significant effects on Corporate Value through Investment Opportunity variable. Simultaneously, all independent variables affect 97.45% of Investment Opportunities and amounted to 97.97% of Corporate Value through Investment Opportunities.